Senegal Dairy Genetics (SDG) Project - Adult Female Survey - Marshall, Karen; Baltenweck, Isabelle; Poole, Elizabeth J.; Tebug, Stanly (International Livestock Research Institute, 2023)
The project “Improved food and nutritional security from better utilisation of dairy cattle breed-types types in Senegal” (SDG), is led by the International Livestock Research Institute (ILRI), in partnership with the the Interstate School of Veterinary science and Medicine of Dakar, the University of Helsinki and Agrifood Research Finland. It is funded via the Finnish Government’s FoodAfrica Programme. SDG aims at: a) Determine the most appropriate dairy breed/cross-breed types for peri-urban dairy production systems in Senegal, and disseminate this information; B) Characterise the dairy germplasm production chain, and related policies, and use this information to develop a strategy for strengthened dairy germplasm production and delivery systems and ; C) Enhance local human, institutional and organizational capacity on accessing and promoting different breeds/cross-breeds of livestock. This dataset contains the Adult Female Survey.